Creative Art Therapy to Promote the Mental Health of Refugee Adolescents - Ramadan, Mohannad Saleh (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2025)
Introduction: Creative art therapy (CAT) has been used to help vulnerable groups like refugee adolescents express themselves and improve their mental health following displacement. It has become increasingly popular to promote positive mental health when accompanied by interdisciplinary interventions that engage families and communities. However, CAT practices and the evidence base supporting their efficacy with refugee adolescents have not been explored within the academic literature. There were no frameworks or guidelines to inform CAT development and delivery. The overarching aim of this research work is to understand the CAT intervention designs, adaptations, and practices that work best to engage refugee adolescents aged 10-24 and promote their mental health. Methodology: First, following a systematic review study design, I searched the grey and black literature published in English and Arabic between 2012 and 2022 across10 databases. Second, a three-round Delphi design was proposed. The first round included semi-structured interviews with an expert panel of 12 CAT professionals worldwide and 12 refugee adolescents aged 1024 in Jordan with a history of participating in creative arts interventions. The interview narratives were analysed through a hybrid approach of coding and thematic analysis, using NVivo, to describe themes of CAT adaptation to the context of refugee adolescents, and to generate statements for use in the second round. In the second round, previous round participants and newly enrolled professionals and refugee adolescents were asked to rate the statements generated from the interviews according to their importance using a 5-point Likert scale. Participants were also invited to propose new statements and to add comments expanding on their rating of the statements. A similar procedure was followed in the third round, where panellists rated newly added and old statements after perusing the feedback from the second round. A consensus is defined as agreement from >= 80% of a panel group, while a below-consensus agreement is between 60% and less than 80%, and a low agreement is <60%. Essential statements obtained consensus by both panels, non-recommended statements had low agreement by both panels, conflicts had low agreement by only one group, and very important had below-consensus agreement from a group and same or consensus by the other. Conflicts in second round were moved to third round with their agreement scores and panellists comments for further discussion and re-rating. Results The systematic review identified 212 documents, but only five articles met the inclusion criteria. These studies reported some positive psychosocial outcomes, but the evidence supporting the effectiveness of CAT as a diagnostic and mental health promotion intervention was inconclusive. CAT specific components and practices were also inconsistent and inadequately reported. The qualitative analysis of interview data gathered during round one of the Delphi identified four themes relating to adaptation: Stability, Enablement, Inclusion, and Integration. The Stability theme is grounded in creating a feeling of safety, security, and confidentiality, mitigating stress for refugee adolescents, and fostering a sense of control and ownership over their artwork. The theme of Enablement is centred around empowering individuals by promoting learning and skills development while adhering to supportive rules that offer equal opportunity to express themselves and enhance self-agency. The theme of Inclusion refers to holistic approaches considering age
APPROVED
Keywords: Creative art therapy; Mental health; Refugee adolescents